Pengembangan Media Pembelajaran Berbasis Web Google Sites Terintegrasi Game Educaplay Pada Materi Peta, Pengindaraan Jauh, Dan Sistem Informasi Geografis (SIG) Di SMA Negeri 1 Suwawa Timur - Tarawe, Nurain; Eraku, Sunarty Suly; Pratama, M. Iqbal Liayong (Universitas Negeri Gorontalo, 2026)
In the era of digitalization, educators’ ability to utilize technology has become an essential competency that must be continuously developed. Teachers are expected not only to have strong technological skills but also to be design and develop innovative, creative, and engaging learning media in order to keep pace with rapid technological advancements. This study aims to develop and evaluate the feasibility of a web-based learning medium using Google Sites integrated with Educaplay games on the topics of Maps, Remote Sensing, and Information Systems. The study was conducted at SMA Negeri 1 Suwawa Timur and involved 26 students as research subjects. The research method employed was Research and Development (RD). The feasibility of the learning media was assessed through validation by media experts, subject matter experts, and learning practitioners, as well as through student responses as media users. The results showed that the learning media obtained a feasibility percentage of 90.2% from media experts, 80% from subject matter experts, and 79.3% from practitioners. In addition, student responses indicated a very high level of acceptance with a percentage of 88.1%. Based on these results, the Google Sites–based learning media integrated with Educaplay games is deemed feasible to be used as a supporting medium for Geography learning.